Treatment of Latent Tuberculosis Infection-An Update - Huaman, Moises A; Sterling, Timothy R (Clinics in chest medicine, 2019)
Treatment of latent tuberculosis infection (LTBI) is an important component of TB control and elimination. LTBI treatment regimens include once-weekly isoniazid plus rifapentine for 3 months, daily rifampin for 4 months, daily isoniazid plus rifampin for 3-4 months, and daily isoniazid for 6-9 months. Isoniazid monotherapy is efficacious in preventing TB disease, but the rifampin- and rifapentine-containing regimens are shorter and have similar efficacy, adequate safety, and higher treatment completion rates. Novel vaccine strategies, host immunity-directed therapies and ultrashort antimicrobial regimens for TB prevention, such as daily isoniazid plus rifapentine for 1 month, are under evaluation.